Tunable laser optics - Duarte, F. J. (CRC Press Taylor & Francis Group, 2015)
Tunable Laser Optics offers a transparent and comprehensive treatment of the physics of tunable laser optics based on a detailed description of first principles. Authored by a leading expert in the field, the book covers the optics and optical principles needed to build lasers, the optics instrumentation necessary to characterize laser emission, and laser-based optical instrumentation, addressing key topics such as Dirac's notation, the interferometric equation, the uncertainty principle, pulse compression, and tunable narrow-linewidth lasers